The Determinants of Economic Growth in the Philippines : A New Look - Tolo, Willa Boots J. (Washington, D.C. : International Monetary Fund, 2011)
This paper uses a panel of 23 emerging markets for the period 1965?2008 to study the determinants of per capita GDP growth in the Philippines. The Philippines is an outlier in terms of agricultural exports, investment, research and development, population growth, and political uncertainty. Panel regressions reveal that these factors, along with the deficit, inflation, trade openness, the current account balance and the frequency of crisis episodes are siginificant determinants of growth. A growth index confirms that these determinants also capture the absolute and relative performance of each country over time and suggests that the Philippines has lacked a sustained period of relatively strong economic reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet